Portrayal of a Closeted Gay in Love Simon Movie - Umayam, Onika Mariel; Aurelia, Gernie Anne; Bada, Ray Patrick; Bartolome, Justine; Maglasang, Josiah Mari; Palantog, Arwen Faye; Rocero, John Christian; Sanita, John Lloyd (Formosa Journal of Multidisciplinary Research, 2024)
The study applied Sigmund Freud's psychoanalytic theory to analyze the experiences of Simon Spier, the closeted gay protagonist of the 2018 film "Love, Simon." Using the concepts of the id, ego, and superego, Simon's internal struggles and external challenges related to his sexual identity, highlighting his fear of being outed, internal conflicts about coming out, and journey towards self-acceptance were examined. The research found that Simon’s portrayal can positively influence viewers’ attitudes towards LGBTQIAP+ individuals by showcasing the complexities of a closeted gay teenager’s life. The study underscored the importance of media in shaping societal perceptions and promoting tolerance, suggesting future research could examine other characters and sexual identities in the novel to understand their impact on readers' views.